Migrant Family - Dorothea Lange:::Creator::::::::::::
A print of a migrant family, including a man and a woman with a baby breastfeeding. Hard copy is high quality photocopy. Lange's photographs influenced the development of documentary photography and humanized the consequences of the Great Depression.